NGTS and WASP photometric recovery of a single-transit candidate from TESS. Issue 2 (19th November 2019) - Gill, Samuel; Bayliss, Daniel; Cooke, Benjamin F; Wheatley, Peter J; Nielsen, Louise D; Lendl, Monika; McCormac, James; Bryant, Edward M; Acton, Jack S; Anderson, David R; Belardi, Claudia; Bouchy, François; et al.
ABSTRACT: The Transiting Exoplanet Survey Satellite ( TESS ) produces a large number of single-transit event candidates, since the mission monitors most stars for only ∼27 d. Such candidates correspond to long-period planets or eclipsing binaries. Using the TESS Sector 1 full-frame images, we identified a 7750 ppm single-transit event with a duration of 7 h around the moderately evolved F-dwarf star TIC-238855958 ( T ma g = 10.23, T eff = 6280 ± 85 K). Using archival WASP photometry we constrained the true orbital period to one of three possible values. We detected a subsequent transit-event with NGTS, which revealed the orbital period to be 38.20 d. Radial velocity measurements from the CORALIE Spectrograph show the secondary object has a mass of M 2 = 0.148 ± 0.003 M⊙, indicating this system is an F–M eclipsing binary. The radius of the M-dwarf companion is R 2 = 0.171 ± 0.003 R⊙, making this one of the most well characterized stars in this mass regime. We find that its radius is 2.3σ lower than expected from stellar evolution models.